A cradle-to-gate life cycle assessment of primary aluminium production at Norðurál - Anna Margrét Kornelíusdóttir 1976- (2014)
Primary aluminium production is an energy intensive process. While the proportion of fossil fuels as main global energy sources for aluminium production has grown in recent years due to China’s increased market share as a producer, Iceland’s importance remains as a producer of renewable energy. The promotion of efficient use of material and energy resources and reduction of waste emissions to air, water and soil are becoming great priorities on the environmental global agenda, for industry and among governments and the public as well. This is also the case in Iceland, where life cycle assessment is becoming a more widespread tool for the assessment of environmental impacts and the identification of environmental hot spots, covering the life cycle of products and services. This is the first time a life cycle assessment is conducted and disclosed to the aluminium industry in Iceland. Two cradle-to-gate life cycle assessments were conducted in order to compare the environmental impacts of the production stages of one metric tonne of primary aluminium at Norðurál with those of an average European smelter, using life cycle inventory data from the European Aluminium Association. By assessing eight different environmental impact categories, it was found in the study that the production of aluminium at Norðurál creates less potential impacts to the environment with regard to global warming, eutrophication, ozone layer depletion and abiotic resource depletion for fossil fuels but not with regard to acidification, photochemical ozone creation, abiotic resource depletion of elements and, finally, primary energy demand of renewable and non-renewable resources. While the energy requirement for primary aluminium remains the source of the industry‘s greatest environmental burden, this does, inevitably, also present a challenge for stewardship and responsible consumption of resources.